AL-ADAB AL-ARABY AL-KLASIKY: BAINA AL-MA'NA AL-LUGAHWI WA AL-MA'NA AL-SIYAQY - Amalia Lailatul Muna; Akmaliyah . (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research explores the deep meanings in classical Arabic literature while considering the socio-cultural context. The primary focus is on the changes in meaning and symbolism in literary works over time. Through a contextual semantic approach, the researcher analyzes classical Arabic literary texts to reveal the relationship between literal and contextual meanings, as well as the influence of symbolism on text comprehension. The research findings indicate that meanings in classical Arabic literature are significantly influenced by social and cultural contexts. The symbols used in literature have deeper meanings and often reflect the values and beliefs of society at that time. Additionally, the changes in the meanings of words and symbols over time are also highlighted in this study. Thus, this research makes an important contribution to understanding the complexity of meanings in classical Arabic literature and their relationship with the socio-cultural context